2017
DOI: 10.1002/mgg3.302
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing and DNA methylation analysis in a clinical amyotrophic lateral sclerosis cohort

Abstract: BackgroundGene discovery has provided remarkable biological insights into amyotrophic lateral sclerosis (ALS). One challenge for clinical application of genetic testing is critical evaluation of the significance of reported variants.MethodsWe use whole exome sequencing (WES) to develop a clinically relevant approach to identify a subset of ALS patients harboring likely pathogenic mutations. In parallel, we assess if DNA methylation can be used to screen for pathogenicity of novel variants since a methylation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
(111 reference statements)
2
14
0
Order By: Relevance
“…For familial probands, 38% (5 out of 13) were carriers of a likely causal variant. This is on the lower end of the range (30–70%) compared to what has previously been reported in European ancestry populations [ 35 , 40 ]. The lower proportion of identified likely causal variants in both sALS and fALS cases is likely to be explained by a lower prevalence of the C9orf72 repeat expansion which accounts for up to 7% of sALS and 40% of fALS in European populations [ 2 ] compared to just 0.3% in sALS cases in this study (as found in other Chinese samples [ 41 , 42 ]).…”
Section: Resultssupporting
confidence: 47%
See 4 more Smart Citations
“…For familial probands, 38% (5 out of 13) were carriers of a likely causal variant. This is on the lower end of the range (30–70%) compared to what has previously been reported in European ancestry populations [ 35 , 40 ]. The lower proportion of identified likely causal variants in both sALS and fALS cases is likely to be explained by a lower prevalence of the C9orf72 repeat expansion which accounts for up to 7% of sALS and 40% of fALS in European populations [ 2 ] compared to just 0.3% in sALS cases in this study (as found in other Chinese samples [ 41 , 42 ]).…”
Section: Resultssupporting
confidence: 47%
“…2 ). This was slightly lower than the proportion of ALS cases with a known causal variant in an Australian clinical ALS cohort (~ 90% European ancestry) which was 10% using an identical filtering technique [ 35 ]. For familial probands, 38% (5 out of 13) were carriers of a likely causal variant.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations